Kinetic Study of Styrene Oxidation over Titania Catalyst Supported on Sulfonated Fish Bone-derived Carbon - Ratna Kusumawardani; Mukhamad Nurhadi; Teguh Wirawan; Anton Prasetyo; Nabila Nur Agusti; Sin Yuan Lai; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The kinetic evaluation of titania supported sulfonated fish bone-derived carbon (TiO2/SFBC) as a catalyst in styrene oxidation by aqueous hydrogen peroxide was carried out. The catalysts were prepared by carbonation of fishbone powder at varying temperatures 500, 600 and 700 °C, respectively for 2 h, followed by sulfonation with sulfuric acid (1M) for 24 h and impregnated by varied titania concentration 500, 1000 and 1500 µmol. The physical properties of catalysts were characterized using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX) and the nitrogen adsorption-desorption analysis. The catalytic activity result showed that TiO2/SFBC can be used as a potential catalyst in styrene oxidation. Worth noting that the sulfonation process has not only transformed the TiO2/FBC particulates (without sulfonation) to cuboid-shaped TiO2/SFBC (with sulfonation) but also contributed to the high selectivity of benzaldehyde. On the other hand, carbonization at different temperatures has an indistinct effect on catalytic performance due to their similar surface areas. The styrene conversion rate responded positively with the increasing amount of titania in the functionalized composites. The styrene oxidation by aqueous H2O2 unraveled the first-order reaction with the activation energy of ⁓63.5 kJ. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).